2020
DOI: 10.1101/2020.07.17.20155226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of climatic, demographic and disease control factors on the transmission dynamics of COVID-19 in large cities worldwide

Abstract: We are now over seven months into a pandemic of COVID-19 caused by the SARS-CoV-2 virus and global incidence continues to rise. In some regions such as the temperate northern hemisphere there are fears of "second waves" of infections over the coming months, while in other, vulnerable regions such as Africa and South America, concerns remain that cases may still rise, further impacting local economies and livelihoods. Despite substantial research efforts to date, it remains unresolved as to whether COVID-19 tra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 73 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…The relationship between COVID-19 and environmental factors is complex [ 78 , 115 ]. Recent studies have demonstrated a positive correlation between spread and decay of SARS-CoV-2 and temperature, absolute humidity and population density [ 116 ] and a positive correlation between the transmissibility of the SARS-CoV-2 and lower UV radiation, lower latitudes, lower elevation, and smaller populations with historical air pollution exposure [ 117 ]. No association was detected between deaths and country temperature or precipitation [ 118 ].…”
Section: Evidence Of the Syndemic Nature Of The Sars-cov-2 Pandemicmentioning
confidence: 99%
“…The relationship between COVID-19 and environmental factors is complex [ 78 , 115 ]. Recent studies have demonstrated a positive correlation between spread and decay of SARS-CoV-2 and temperature, absolute humidity and population density [ 116 ] and a positive correlation between the transmissibility of the SARS-CoV-2 and lower UV radiation, lower latitudes, lower elevation, and smaller populations with historical air pollution exposure [ 117 ]. No association was detected between deaths and country temperature or precipitation [ 118 ].…”
Section: Evidence Of the Syndemic Nature Of The Sars-cov-2 Pandemicmentioning
confidence: 99%
“… Relation Country Statistical method used Ref. Negative Global (≥50 countries) Mapping to Köppen's climate ( Bajaj and Arya, 2020 ) Spearman correlation ( Bezabih et al, 2020 ) Simple LR model; Pearson correlation ( Hassan et al, 2020 ) Simple LR model ( Iqbal et al, 2020 ) Multivariate LR model ( Luo et al, 2020 ) Stepwise LR model ( Metelmann et al, 2020 ) Simple LR model ( Notari, 2021 ) Mann-Whitney test; LR model ( Sajadi et al, 2020 ) Pearson correlation ( Sarmadi et al, 2020 ) Gutenberg–Richter law model ( Sil and Kumar, 2020 ) Uni/Multivariate LR model (by panel data strategy) ( Sobral et al, 2020 ) GAM ( Wu et al, 2020b ) Brazil GAM; Polynomial regression model ( Prata et al, 2020 ) Shapiro-Wilk test; Spearman correlation ( Rosario et al, 2020 ) China SEIR model with simple LR model; Pearson correlation ( Guo et al, 2020 ) Multivariate Poisson regression model …”
Section: Introductionmentioning
confidence: 99%
“…In another simple LR analysis, average high temperature was reciprocally related to both total deaths (β = -0.0377, R 2 = 0.4192) and total cases per million population (β = -0.0037, R 2 = 0.5875) ( Iqbal et al, 2020 ). A stepwise LR model fitted with R 0 displayed a negative relationship between temperature and SARS-CoV-2 infectivity ( Metelmann et al, 2020 ). Fitting a simple LR on the exponential spread rate with the average temperature again exhibited a decreasing slope (β = -0.0035, R 2 = 0.18) ( Notari, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations